Autonomous Drug Release Systems with Disease Symptom‐Associated Triggers. (5th February 2020) - Xiong, Ya; Qi, Lin; Niu, Ye; Lin, Yueqiang; Xue, Qingzhong; Zhao, Yi
Abstract : Many biophysical and biochemical properties of pathogenic tissues are different from those of healthy tissues. These disease symptom‐associated properties include pH, reduction–oxidation conditions, enzyme generation and expression, blood glucose concentration, mechanical stiffness and strain, and temperature. Autonomous drug release that uses one or more of these disease symptom‐associated properties as the release trigger minimizes the delay in treatments and allows for the release of medications with precisely controlled amounts and with desired spatiotemporal patterns. Herein, a comprehensive assessment of current research progress on autonomous drug release systems (ADRS) is provided. The representative symptoms‐associated properties that can be potentially used as the endogenous stimuli are introduced. The autonomous drug systems that utilize these symptom‐associated signals as the endogenous stimulation signals are discussed, followed by the discussion of current challenges and opportunities in this field, as well as possible future directions in ADRS. Abstract : Some disease symptoms carry notable changes in biophysical and biochemical properties. Autonomous drug release using one or more of these endogenous signals as the triggers to release drugs can minimize the delay in treatments and allow for the release of medications with precisely controlled amounts and desired spatiotemporal patterns.